PERAN GEMBALA MENURUT YOHANES 21:15-17 STUDI KASUS DI GBI BIG JAKARTA: Penggembalaan - Rikardo Sianipar; Herifeka (STT Bethel The Way, 2020)
This research aims to clearly understand the role of the pastor in a biblical manner in GBI BIG Jakarta, so that it is carried out in increasing, providing spiritual food, and visits, within the congregation. The role of the pastor is very important for the spiritual growth of the church, so that it is in accordance with the Word of God so that the congregation will grow and mature spiritually that is good and true. At GBI Bless Impact Generation, the pastor always provides healthy benefits to open the congregation's insight about the Word of God. This research was conducted using descriptive methods, focusing on an object by studying a case. The researcher concluded that the role of pastors in GBI Bless Impact Generation is carried out by learning and being able to change congregations to practice God's truth. The congregation can be nurtured and the shepherding goes well.